Interaction of proteins with oligo(ethylene glycol) self-assembled monolayers - Skoda, M; Skoda, Maximilian (2007)
﻿ The aim of this thesis is the study of protein resistant oligo(ethylene glycol) (OEG) self-assembled monolayers (SAMs) using in situ techniques, such as neutron reflectivity (NR), polarisation modulation infrared spectroscopy (PMIR) and small-angle x-ray scattering (SAXS). In order to elucidate the mechanisms that lead to the nonfouling properties of these SAMs, the SAM-water, protein-protein and protein-SAM interactions have been studied separately. NR measurements, focused on the solid-liquid interface between OEG SAMs and water, show clear evidence of an extended layer with reduced density water. The reduction in density is up to 10% compared to the bulk value, and extends up to 5 nm into the bulk. The effective area (density reduction x length) of this reduced density water layer did not significantly change when the temperature was reduced to 5°C. In a complementary study, the interaction of water with protein-resistant HS(CHV2)11(OCH2CH2)3OMe monolayers was examined using in and ex situ PMIR. In particular, shifts in the position of the characteristic C-O-C stretching vibration were observed after the monolayers had been exposed to water. The shift in frequency increased when the SAM was observed in direct contact with a thin layer of water. It was found that the magnitude of the shift also depended on the surface coverage of the SAM. These results suggest a rather strong interaction of oligo(ethylene glycol) SAMs with water and indicate the penetration of water into the upper region of the monolayer. These findings indicate the presence of a tightly bound water layer at the SAM-water interface. Further NR studies of the interface between OEG SAMs and a highly concentrated protein solution revealed an oscillating protein density profile. A protein depleted region of about 4-5 nm close to the SAM was followed by a more densely populated region of 5-6 nm. These oscillations were then rapidly damped out until the bulk value was reached. The influence of temperature and salt concentration on the protein density profile was small, indicating a rather minor contribution of electrostatic interactions to the protein repulsive force. SAXS measurements of OEG coated gold colloids mixed with proteins in solution did also not show any pronounced salt concentration dependence of the colloid-protein interaction. The strong association of water with the SAM and the layer of tightly bound water, together with the lack of electrostatic repulsion, suggest that the adsorption of proteins is energetically hindered by the presence of a strongly bound hydration layer.